Comparative analysis of the verbalization of the concepts of nation and personality in English and Uzbek linguocultures - Burieva, Nilufar Gofurovna (The Lingua Spectrum, 2026)
The article presents a comparative analysis of the verbalization of the concepts of nation and personality in English and Uzbek linguocultures. The study aims to identify similarities and differences in the linguistic means used to express these concepts and to reveal their cultural and cognitive significance. Attention is given to lexical units, phraseological expressions, and contextual interpretations reflecting national and individual identity. The research is based on dictionary definitions, authentic literary and media texts, and selected discourse examples, which allows tracing how the concepts are represented in different communicative situations. The study also considers the influence of historical, social, and cultural factors on the formation and transformation of these concepts in English and Uzbek linguocultural space. Emphasis is placed on the interaction between language and culture in shaping collective and personal worldviews. The purpose is to determine key linguocultural patterns and explore their practical application in foreign language teaching, translation studies, and intercultural communication. The findings contribute to understanding how language encodes cultural values and identities in both languages.